New synonyms and new combinations for some Delphacidae (Hemiptera, Auchenorrhyncha) of Eastern and Central Palaearctic Region - Emeljanov, Alexandr F. (Zootaxa, 2019)
Five new generic and 7 species synonyms and 3 new combinations are proposed for the tribe Delphacini. Atropidius Emeljanov 1982, is placed in synonymy under Glabrinotum Ding, 2006, in so far as Atropidius Emeljanov is homonym of Atropidius Chapui. Stiropis Ding, 2006—under Cormidius Emeljanov, 1972, Metroma Ding, 2006—under Metropidius Emeljanov, 1972, Mengdelphax Ding, 1994—under Movesella Emeljanov, 1982, and Paramestus Ding, 2006—under Pastiroma Dlabola, 1967. Glabrinotum qitaiensis Ding, 2006 is placed in synonymy under Glabrinotum lapilla (Emeljanov, 1982), Mengdelphax neimengensis Ding & Zhang, 1994—under Movesella nuchtica (Dlabola, 1967), Calligypona minutissima Dubovsky, 1966—under Falcotoya minuscula (Horváth, 1897), Calligypona uzbekistanica Dubovsky, 1966—under Flastena fumipennis (Fieber, 1866), Chloriona adunca Ding, 1981—under Paradelphacodes gvosdevi (Mitjaev, 1980), Calligypona brunneola Dubovsky, 1966—under Paradelphacodes paludosus (Flor, 1861), and Calligypona tricolorata Dlabola, 1961 and Delphacodes fenestratus Emeljanov, 1972—under Pseudodelphacodes flaviceps (Fieber, 1866). Elachodelphax xingjiangensis Chen, 2002 is transferred to Scottianella Anufriev, 1980 and Paramestus nigroclypeus Ding, 2006 and Mestus nigrostriatus Ding & Zhang, 2000—to Pastiroma Dlabola, 1967.